Overview of the use of clean cookstoves in the Brazilian semiarid region (Sustainability in Debate, 2019)
Wood cookstoves are common in the Brazilian semiarid region. Most families use traditional versions,which have a series of social, environmental and health-related impacts. “Improved cookstoves” referto cleaner and more efficient cookstoves. These include adaptations that improve energy efficiency and reduce indoor air pollution, bringing benefits such as the reduction of firewood consumptionfor cooking, reduction of the emission of polluting gases originating from firewood burning andfewer health impacts, also contributing to forest conservation. Although the improved cookstovessector is still relatively underdeveloped in the Brazilian semiarid region, in recent years interest inthese technological alternatives has increased. In this context, the present study contributes to thecompilation and organization of information referring to the use of improved cookstoves in the Braziliansemiarid region.